Growth and male reproduction improvement of non-thermal dielectric barrier discharge plasma treatment on chickens. (27th April 2018) - Zhang, Jiao Jiao; Huynh, Do Luong; Chandimali, Nisansala; Kang, Tae Yoon; Kim, Nameun; Mok, Young Sun; Kwon, Taeho; Jeong, Dong Kee
Abstract: This study investigated whether plasma treatment of fertilized eggs before hatching could affect the growth and reproduction of chickens. Three point five-day-incubated fertilized eggs exposed to non-thermal dielectric barrier discharge plasma at 2.81 W of power for 2 min resulted in the highest growth in chickens. Plasma growth-promoting effect was regulated by the reactive oxygen species homeostasis and the improvement of energy metabolism via increasing serum hormones and adenosine triphosphate levels which were resulted from the regulation of genes involved in antioxidant defense, hormone biosynthesis and energetic metabolism. Interestingly, plasma-treated male chickens conspicuously grew faster than females. Further, aspects of male reproductive system (testosterone level and sperm quality) were improved by the plasma treatment but female reproduction (estradiol and progesterone levels, egg-laying rate and egg weight) had no significant changes. Unfortunately, offspring whose parents were the optimal plasma-treated chickens did not show any difference on growth characteristics and failed to inherit excellent growth features from their parents. Our results suggest a new method to improve the growth rate and male reproductive capacity in poultry but it is only effective in the plasma direct-treated generation.